Automated parking management system for identifying vehicle number plate - Asha Singh; Prasanth Vaidya (Institute of Advanced Engineering and Science, 2019)
By using image processing, the Automated parking management system (APMS) to recognize the license plate number for efficient management of vehicle parking and vehicle billing. It is an independent real-time system, reduces number of people involvement in parking areas. The main aim of this system is to automated payment collection. This (APMS) system extract and recognize license plate numbers from the vehicles, then that image is being processed and used to generate an electronic bill. Generally in the parking lots heavy labor work is needed. This system used to decrease the cost of the labor and also enhance the performance of the APMS. This system is composed of vehicles license plate number extraction, character segmentation and character recognition. A proper pre-processing is done before extracting the license plate and it also generates the entry time and exit time of the vehicle and finally generates the electronic bill.